COVID-19 Pandemic: Effect of prolonged lockdown on adolescents and young adults - Pande, Devina; Parekh, Zahi; Kanhere, Sujata (Indian Journal of Child Health, 2024)
Objective: This study was conducted to assess the impact of the prolonged lockdown, due to the Coronavirus Disease 2019 (COVID-19) pandemic, on the daily life, education, mental and family health, and general well-being of adolescents and young adults in India. Materials and Methods: A total of 210 participants aged 12–21 years formed the study sample. After approval from the Institutional Ethics Committee, a cross-sectional study was conducted using a pre-designed validated online questionnaire. Consent/assent was taken and confidentiality was assured. The questionnaire consisted of 33 questions. The data were analyzed using Microsoft Excel, expressed as frequency and percentages, and converted to charts and graphs. Results: Most (88%) of the respondents understood the severity of the pandemic. The majority (85%) of educational institutions conducted online classes; however, classroom lectures were preferred over online lectures by 171 (81.4%) students. Thirty-seven (36.7%) students had been affected by the cancellation of entrance exams. Eagerness to return to school/college was found amongst 135 (64.2%) participants. Lockdown restrictions led to 56% of activities being screen-based, leading to headaches and eye strain in 167 (79.5%) students. Participants were bored, irritated, and anxious, but 56.2% of them remained positive by developing new hobbies, reading, or spending time with family. Sixty-nine (32.8%) respondents or their close family members suffered from mild COVID symptoms; however, it was a major strain on their mental health. Conclusion: Overall, the pandemic and prolonged lockdown had a mixed impact on 82 (39%), a negative impact on 65 (31%), and a positive impact on 63(30%) of adolescents and young adults.